2007
DOI: 10.1021/bi0620757
|View full text |Cite
|
Sign up to set email alerts
|

The Specificity in the Interaction between Cytochrome f and Plastocyanin from the Cyanobacterium Nostoc sp. PCC 7119 Is Mainly Determined by the Copper Protein

Abstract: The plastocyanin-cytochrome f complex from Nostoc exhibits relevant structural differences when compared with the homologous complexes from other cyanobacteria and plants, with electrostatic and hydrophobic interactions being differently involved in each case. Here, five negatively charged residues of a recombinant form of cytochrome f from Nostoc have been replaced with either neutral or positively charged residues, and the effects of mutations on the kinetics of electron transfer to wild-type and mutant form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
20
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 32 publications
(91 reference statements)
2
20
1
Order By: Relevance
“…21,22 Clearly, the hydrophobic patch plays a fundamental role in the formation of the Cyt f-Pc complexes. The CSP map is qualitatively similar to that of the N−N complex 22,27 with a prominent perturbation for R93, known to be involved in the binding in both the N−N complex 18,19,22 and Ph-Ph complex. 16 Interestingly, a significant CSP was also observed for K46 in the N-Ph complex.…”
mentioning
confidence: 59%
“…21,22 Clearly, the hydrophobic patch plays a fundamental role in the formation of the Cyt f-Pc complexes. The CSP map is qualitatively similar to that of the N−N complex 22,27 with a prominent perturbation for R93, known to be involved in the binding in both the N−N complex 18,19,22 and Ph-Ph complex. 16 Interestingly, a significant CSP was also observed for K46 in the N-Ph complex.…”
mentioning
confidence: 59%
“…The solution models of the complexes have been determined by rigid-body docking of the structures of the individual proteins on the basis of binding chemical shift perturbations and intermolecular pseudocontact shifts (PCSs) of Pc nuclei induced by the paramagnetic, oxidized iron of Cyt f [10][18] or negative charges on Cyt f [19] resulted in a decreased association rate constant. It could be shown that for Pc several charges are pivotal for the interaction [18 , 19].…”
Section: Introductionmentioning
confidence: 99%
“…In the case of the Nostoc complex, site-directed mutagenesis studies on the influence of charges on the kinetics of complex formation highlighted how the loss of either positive charges on Pc[18] or negative charges on Cyt f [19] resulted in a decreased association rate constant. It could be shown that for Pc several charges are pivotal for the interaction [18 , 19]. On the other hand, the charges on Cyt f are more spread out over the surface, and no “hot spots” were identified in either Nostoc [19] or P. laminosum, [15] thus suggesting that the encounter state might have an important role in these complexes.…”
Section: Introductionmentioning
confidence: 99%
“…Pc is a small, soluble cupredoxin that shuttles electrons from Cf to photosystem I [2,3]. The structure of Pc is a betabarrel with two functional surface areas [2,3,[7][8][9]: one hydrophobic surrounding a copper-ligand histidine (site 1), and the other electrostatically charged (site 2). Cf, in its turn, is a subunit of cytochrome b 6 f [6] that is anchored to this membrane complex by its hydrophobic, C-terminal alpha-helix.…”
Section: Introductionmentioning
confidence: 99%
“…The electron transfer from Cf to Pc has been analysed by using stopped-flow [11][12][13][14][15] and fast kinetic techniques [7,16], often combined with site-directed mutagenesis of one or both partners. The resulting kinetic data have been very useful to analyse the interaction between Pc and Cf by means of theoretical methods, including Molecular Dynamics (MD) at sub-nanosecond time scale [17], rigid-body MD [18], Molecular Modelling [19] supported by NMR data and Brownian Dynamics (BD) simulations [20][21][22][23][24][25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%